Efficient synthetic supramolecular channels and their light-deactivated ion transport in bilayer lipid membranes1. (27th August 2015) - Bao, Chunyan; Ma, Meixin; Meng, Funa; Lin, Qiuning; Zhu, Linyong
<x xml:space="preserve">Abstract</x> Efficient ion transport and photo-deactivation was achieved from the self-assembled channel of o-nitrobenzyl-based amphiphilic small molecules.